Diseño de una propuesta para crear el área de gestión del talento humano en el restaurante Hero Express Gourmet (2017)
Currently we live in a highly competitive society, where organizations propose strategies and gather the best possible human capital to be at the forefront of their competitors. One of the key factors for an organization to be successful and sustainable over time, is the human talent of that organization. In the service sector, specifically the food and beverage sector, to which Belongs, the organization Hero Express Gourmet, is a very competitive and saturated sector, so it is essential to have the best human talent to be sustainable over time and To be profitable.